Le «Mégas Chronographos» et Procope - Greatrex, Geoffrey (Revue des études byzantines, 2023)
This article, based on a detailed comparison of the ninth entry of the 'Megas Chronographos' and chapters 22-23 of Procopius’ Wars, establishes that the chronicler drew his account, whether directly or indirectly, from that of the historian: until now no one had identified the source of this entry. The discovery is of some importance, given the great attention now being paid to the Justinianic plague. In this context, the chronicler’s notice has often been perceived as an independent source, which now is shown to be no longer possible.